2021
DOI: 10.3390/su13041949
|View full text |Cite
|
Sign up to set email alerts
|

Student Long-Term Perception of Project-Based Learning in Civil Engineering Education: An 18-Year Ex-Post Assessment

Abstract: In 1998, the Universidad de Castilla-La Mancha (UCLM) began to offer a 5-year civil engineering degree that, in the Spanish context, contained an innovative teaching model, which was characterized by a reduced number of students and project-based learning (PjBL) included in the curriculum. Now, 15 years after the graduation of the first civil engineers from the UCLM, graduates were given a questionnaire to evaluate the extent by which the advantages described in the PjBL literature were perceived as such by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
(33 reference statements)
2
17
0
1
Order By: Relevance
“…Similar beneficial outcomes were observed in other disciplines in high education, such as active student participation, foster contact with reality, an increased perception of the acquisition of generic and specific skills associated with the subject, and confidence in problem-solving [42][43][44]. More specifically, a study conducted with civil engineers 15 years after graduation revealed that PBL-related abilities developed at the university (ability to work in groups, communication/debate skills, and leadership) were appreciated by students who followed PBL methodology and considered their learning to be more effective and with a better result-to-effort ratio than those who did not [45].…”
Section: Transport Infrastructurementioning
confidence: 99%
“…Similar beneficial outcomes were observed in other disciplines in high education, such as active student participation, foster contact with reality, an increased perception of the acquisition of generic and specific skills associated with the subject, and confidence in problem-solving [42][43][44]. More specifically, a study conducted with civil engineers 15 years after graduation revealed that PBL-related abilities developed at the university (ability to work in groups, communication/debate skills, and leadership) were appreciated by students who followed PBL methodology and considered their learning to be more effective and with a better result-to-effort ratio than those who did not [45].…”
Section: Transport Infrastructurementioning
confidence: 99%
“…PjBL has become one of the most widely adopted innovative teaching strategies for facing future challenges [10]. Mills and Treagust [11] pointed out that PjBL is the teaching strategy centered around students and focuses on interdisciplinary comprehension and application.…”
Section: Engineering-centered Pjblmentioning
confidence: 99%
“…PjBL has become one of the most widely adopted innovative teaching strategies for facing future challenges [10]. Mills and Treagust [11] pointed out that PjBL is a teaching strategy centred around students and focuses on interdisciplinary comprehension and application.…”
Section: Engineering-centered Pjblmentioning
confidence: 99%